Evaluation of galantamine and deconstructed analogs as α7 nAChR and AChE ligands - Malaika D. Argade; Laura DeCristofano; Nirajan Bhattarai; Marvin K. Schulte; Malgorzata Dukat (Results in Chemistry, 2022)
Galantamine (1), one of only five agents currently approved for the treatment of Alzheimer’s disease, is thought to act primarily as an inhibitor of acetylcholinesterase (AChE) and possibly as a positive allosteric modulator (PAM) of neuronal α7 nicotinic acetylcholine (nACh) receptors. Here, the structure of 1 was deconstructed to ten “abbreviated” analogs and examined electrophysiologically at α7 nACh receptors and as inhibitors of AChE. Neither 1, nor its reduced analog lycoramine (3), displayed PAM action, but at high concentrations both inhibited the agonist action of 100 μM ACh. The other deconstructed analogs lacked a PAM effect and also the inhibitory action of 1/3 indicating that the cyclohexa(e)nyl ring and/or hydroxyl group of 1/3 are important for the latter. All of the deconstructed analogs examined behaved as inhibitors of AChE but were >400-fold less potent than 1, again indicating that the cyclohexanol portion of 1 is a major determinant for optimal activity.